2008
DOI: 10.1007/s12010-008-8293-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aeration and Agitation Regimes on Lipase Production by Newly Isolated Rhodotorula mucilaginosa–MTCC 8737 in Stirred Tank Reactor Using Molasses as Sole Production Medium

Abstract: The influence of media and process parameters (aeration and agitation) on fermentation broth rheology and biomass formation has been studied in 1.5-l stirred tank reactor for lipase production using Rhodotorula mucilaginosa MTCC 8737. Molasses, as sole production medium, is used for lipase production by varying aeration (1, 2, and 3 vvm) and agitation speeds (100, 200, and 300 rpm). Maximum lipase activity of 72 U/ml was obtained during 96 h of fermentation at 2 vvm, 200 rpm, pH 7, and 25 +/- 2 degrees C tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 28 publications
1
18
1
Order By: Relevance
“…This could be attributed to the occurrence of mechanical and/or oxidative stress in the cultures. In a similar way, Portumarthi et al 36 found that intermediate conditions of aeration and agitation were the most suitable to obtain lipases in stirred tank cultures of Rhodotorula mucilaginosa-MTCC 8737.…”
Section: Bioreactor Culturementioning
confidence: 86%
“…This could be attributed to the occurrence of mechanical and/or oxidative stress in the cultures. In a similar way, Portumarthi et al 36 found that intermediate conditions of aeration and agitation were the most suitable to obtain lipases in stirred tank cultures of Rhodotorula mucilaginosa-MTCC 8737.…”
Section: Bioreactor Culturementioning
confidence: 86%
“…Although lipases from C. rugosa and C. antarctica have been extensively used in different fields, there are several recent publications reporting the production of lipases by other yeasts, as shown in Table 1. Potumarthi et al (2008) collected marine soil samples near an oil extraction platform in the Arabian Sea. After the isolation of the colonies, they were transferred to plates containing 2% tributyrin and incubated at 35°C for 3-4 days.…”
Section: Filamentous Fungimentioning
confidence: 99%
“…When comparing both tested media, the best results were obtained using the one based on peptone, yeast extract, NaCl, and olive oil. Potumarthi et al (2008) employed molasses as sole carbon source for lipase production by R. mucilaginosa MTCC 8737. A maximum lipase activity was verified using 1% of molasses.…”
Section: Agroindustrial Residuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Response surface methodology (RSM) has been widely used to evaluate and understand the interactions between different process parameters [5]. RSM was applied successfully for optimizing process parameters for various processes in biotechnology [6][7][8][9][10][11][12].…”
mentioning
confidence: 99%